The Efficacy of the Supramolecular Complex of Ivermectin in Production Conditions Against Gastro-intestinal Nematodosis of Herd Horses - M. B. Musaev; V. V. Zashchepkina; S. V. Vatsaev; A. Z. Dzhamalova; M. M. Ilyin; S. S. Khalikov (Российский паразитологический журнал, 2020)
The purpose of the research is to test the efficacy of the supramolecular complex of ivermectin against gastro-intestinal nematodes of herd horses under production conditions. Materials and methods. The test of the efficacy of the supramolecular complex of ivermectin was carried out from December 2018 to January 2019 in the North Caucasus Federal District of the Chechen Republic. Two herds of horses of 47 and 54 heads in each of different ages were selected, which were grazed all year round. To determine the infection of horses with nematodes of gastro-intestinal tract, 20 samples of fresh feces from each group were collected from the ground. It was not possible to collect samples from untamed horses to determine the infection by Oxiuris spp. Coproovoscopy was performed using the Fülleborn method. To count eggs in 1 g of faeces, a VIGIS counting chamber was used. The first group was given a 2.0% drug individually in a mixture with food at a dose of 0.15 mg/kg for active substance (AS) (according to the drug 75 mg). The drug was administered to the second group at a dose of 0.2 mg/kg for AS (for the drug 1.0 mg/kg) by the group method in a mixture with food, calculated on a live weight of 500 kg. The efficacy of the drug was determined 2 weeks after deworming according to coproovoscopy data. The efficacy of ivermectin complex was accounted for by the "critical test" method. After deworming, the animals were observed during the experiment. Results and discussion. Dehelminthization of horses with a supramolecular complex of ivermectin at a dose of 0.2 mg/kg for AS in a mixture with mixed feed by a group method for mixed infection of various types of gastro-intestinal nematodes under production conditions showed 100% efficiency. Arabinogalactan in the supramolecular complex helps to eliminate the negative effect of AS (ivermectin) on the animal body. The mixture of the preparation with the food was readily consumed by the horses. Deworming horses of herd keeping with a preparation intended for use in a mixture with feed is technically convenient, practically uncomplicated, and at the same time, physical exertion during fixation of animals and industrial injuries are excluded. We did not observe any side effects after deworming horses.